Soil Chemical Differences Between Pasture Types in Southern Marmara, Turkey - Hakan Hakyemez, B.; O. Parlak, Altingul; Celik, Sezgin; Gokkus, Ahmet (Asian Journal of Chemistry, 2010)
In this study, the effects of soils on poor yield and condition of pastures in Southern Marmara, Turkey were determined. For this reason, total of 60 soil samples, in Spring 2006, were collected from 5 types of pastures in Canakkale, Balikesir and Bursa provinces, all located in the Southern Marmara region. Pasture types investigated were mountain, shrubland, coastal, lowland and forest gap type pastures. All of the collected soil samples were being evaluated for soil electrical conductivity (EC), pH, CaCO3, P, K, Ca, Mg, Na, Fe, Mn, Zn, Cu and organic matter. The EC (P = 0.000), CaCO3 (P = 0.009), organic matter (P = 0.000), P (P = 0.003), K (P = 0.027), Fe (P = 0.025) and Cu (P = 0.047) levels of soils were significantly different between pastures. Highest levels of EC (1.67 ± 0.82 dS m-1) and of CaCO3 (5.81 ± 1.02 %), were found in the soil samples obtained from coastal region and shrubland type pastures, respectively. However, the highest levels of both organic matter (4.94 ± 0.50 %) and P (49.0 ± 3.4 ppm) were found in both forest gap and lowland type pastures. Cu level was the highest in coastal type pastures among all 5 types of pastures analyzed. Among the provincial pastures, pH (P = 0.009), organic matter (P = 0.007), P (P = 0.002), Ca (P = 0.019), Mg (P = 0.020), Fe (P = 0.000), Zn (P = 0.013) and Cu (P = 0.003) levels of soils were significant. The highest levels of pH (7.40 ± 0.11), of CaCO3 (4.87 ± 0.61 %), of Ca (3049 ± 275 ppm) and of Mg (656.7 ± 60.9 ppm) level were found in pastures of Canakkale province while the highest levels of organic matter (%4.01 ± 0.40), of Fe (22.8 ± 3.0 ppm), of Zn (1.21 ± 0.10) and of Cu (0.92 ± 0.08 ppm) were found in pastures of Bursa province. Overall results of this study indicated that pastures of Southern Marmara region do not have very significant problem in their soil chemical compositions. Therefore, in order to improve these pastures, prescribed grazing management or weed/vegetation management practices should be applied.